Kajian terhadap proses dan pendekatan dalam pembentukan dasar pekerja asing di Malaysia : (Study on the process and approach of the formation of foreign workers policy in Malaysia) - Ajis, Mohd Na’eim; Keling, Mohamad Faisol; Ahmad Zakuan, Ummu Atiyah; Mohd. Zain, Zawiyah (Universiti Kebangsaan Malaysia, 2018)
Demands for foreign workers in Malaysia is inevitable and the government has developed various policies and programmes to control the entry of foreign workers to the country. There are two objectives will be discussed in this article which are first, to examine the process and to analyse the approach used in making policies relating foreign workers. This study adopts qualitative approach, using face-to-face interview with respondents who were selected in this study. They were selected based on their involvement in policy making relating to the foreign workers. The respondents are categorized into two groups, formal and informal. The formal group comprises of Cabinet Committee on Foreign Workers and Illegal Migrant (JKPPA-PATI), while the latter group consists of representatives from employee, employees, NGOs and academics. The findings of this study reveal that there are three stages of foreign worker policy making processes. The first stage involves discussion between ministries with various interest groups such as MEF, MTUC and NGOs. The second stage covers is the discussion between the Ministry of Home and Ministry of Human Resource with other regulatory agencies from other ministries. The last stage is the formal meeting of the JKPPA-PATI Committee. In making foreign worker policy, economic and security approaches are used. It means, every agency which involved in foreign workers has its own consideration and justification on what approach to be used. In conclusion, foreign worker policy making involves different stages of discussion with various stakeholders. The main consideration in making this policy is based on these two main economic and security factors which also appear as the main cause of public policy conflict between the parties involved.